Exposure to attachment narratives dynamically modulates cortical arousal during the resting state in the listener. Issue 7 (6th June 2018) - Borchardt, Viola; Surova, Galina; van der Meer, Johan; Bola, Michał; Frommer, Jörg; Leutritz, Anna Linda; Sweeney‐Reed, Catherine M.; Buchheim, Anna; Strauß, Bernhard; Nolte, Tobias; Olbrich, Sebastian; Walter, Martin
Abstract: Background: Affective stimulation entails changes in brain network patterns at rest, but it is unknown whether exogenous emotional stimulation has a prolonged effect on the temporal dynamics of endogenous cortical arousal. We therefore investigated differences in cortical arousal in the listener following stimulation with different attachment‐related narratives. Methods: Resting‐state EEG was recorded from sixteen healthy subjects for ten minutes each with eyes closed: first at baseline and then after passively listening to three affective narratives from strangers about their early childhood experiences (prototypical for insecure‐dismissing, insecure‐preoccupied, and secure attachment). Using the VIGALL 2.1 algorithm, low or high vigilance stages in consecutive EEG segments were classified, and their dynamic profile was analyzed. Questionnaires assessed the listeners' emotional response to the content of the narrative. Results: As a general effect of preceding affective stimulation, vigilance following the stimulation was significantly elevated compared to baseline rest, and carryover effects in dynamic vigilance profiles were observed. A difference between narrative conditions was revealed for the insecure‐dismissing condition, in which the decrease in duration of high vigilance stages was fastest compared to the other two conditions. The behavioral data supported the observation that especially the insecure narratives induced a tendency in the listener to affectively disengage from the narrative content. Discussion: This study revealed carryover effects in endogenous cortical arousal evoked by preceding affective stimulation and provides evidence for attachment‐specific dynamic alterations of brain states and individual differences in emotional reactivity. Abstract : Affective stimulation entails changes in brain network patterns at rest and has furthermore a prolonged effect on the temporal dynamics of endogenous brain arousal regulation. Listening to affective narratives from strangers about early childhood experiences evoked dynamic carryover effects in endogenous arousal regulation that had attachment‐specific temporal profiles.